2007
DOI: 10.1303/aez.2007.71
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of thrips (Thysanoptera: Thripidae) based on partial sequences of cytochrome oxidase I, 28S ribosomal DNA and elongation factor-1 α and the association with vector competence of tospoviruses

Abstract: The phylogenetic relationships among 16 species including 10 thrips vector species of tospoviruses were analysed using partial sequences of three genes: mitochondrial COI, nuclear 28S ribosomal DNA and the elongation factor-1a (EF-1a) in order to reveal the influence of lineage among thrips vector species on the vector competence of tospoviruses. The phylogenetic trees of thrips suggested that distinct clades were formed between the genera Frankliniella and Thrips including vector species at least in combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Similar effects of plant viruses have also been reported in other insects. For example, the adult lifespan of thelytokous Thrips tabaci is shortened upon infection by Tomato spotted wilt virus (TSWV) (Inoue and Sakurai, 2006). Rubinstein and Czosnek (1997) suggested that the negative effect plant virus infection has on vector longevity is a deleterious feature reminiscent of an insect pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of plant viruses have also been reported in other insects. For example, the adult lifespan of thelytokous Thrips tabaci is shortened upon infection by Tomato spotted wilt virus (TSWV) (Inoue and Sakurai, 2006). Rubinstein and Czosnek (1997) suggested that the negative effect plant virus infection has on vector longevity is a deleterious feature reminiscent of an insect pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…One pair of F. occidentalis ‐specific primers FOCZ‐1F/FOCZ‐1R was designed based on a known mitochondrial cytochrome oxidase I gene sequence (556 bp, GenBank Accession No: ; Inoue and Sakurai 2007) of the western flower thrips. The sequence of the 5′ upstream primer (FOCZ‐1F) was 5′‐TTGACTTCTTCCACCCTCT‐3′, corresponding to the region from bases 20–38, and the 3′ downstream primer (FOCZ‐1R) was 5′‐TGTATTTAAGTTTCGGTCTG‐3′, corresponding to bases 340–359 (Inoue and Sakurai 2007). The primers were synthesized by Shanghai Shenggong Biotechnological Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Two microlitres of extracted DNA was used as the template for PCR. corresponding to bases 340-359 (Inoue and Sakurai 2007). The primers were synthesized by Shanghai Shenggong Biotechnological Ltd (Shanghai, China).…”
Section: Dna Extractionmentioning
confidence: 99%
“…To increase the data set, sequences of species included in the studies of Brunner et al (2002) and Inque & Sakurai (2007) as well as additional species obtained from GenBank ( Fig. 1), were included in statistical analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A system of identifying economically important thrips species present in Europe was developed by Brunner et al (2002), based on nucleotide sequence analysis of the mitochondrial cytochrome oxidase (COI) gene, which has since been confirmed to be a suitable marker for thrips species identification ). More recently, nucleotide sequences of various genes, including the COI gene, of virustransmitting thrips species present in Japan were provided by Inque & Sakurai (2007), as part of an attempt to study the association of viruses with their thrips vectors. However, although several species of thrips of economic importance in South Africa were included in the aforementioned studies, various damaging endemic species lack reliable means of identification.…”
Section: Introductionmentioning
confidence: 99%